Spheroid Formation and Recovery Using Superhydrophobic Coating for Regenerative Purposes - María del Carmen Morán; Francesca Cirisano; Michele Ferrari (Pharmaceutics, 2023)
Cell therapies commonly pursue tissue stimulation for regenerative purposes by replacing cell numbers or supplying for functional deficiencies. To this aim, monodispersed cells are usually transplanted for incorporation by local injection. The limitations of this strategy include poor success associated with cell death, insufficient retention, or cell damage due to shear forces associated with the injection. Spheroids have recently emerged as a model that mimics an in vivo environment with more representative cell-to-cell interactions and better intercellular communication. Nevertheless, cost-effective and lab friendly fabrication and effectively performed recovery are challenges that restrict the broad application of spheroids. In this work, glass surfaces were modified with an environmentally friendly superhydrophobic coating. The superhydrophobic surfaces were used for the 3D spheroid preparation of fibroblasts (3T3 cell line) and keratinocytes (HaCaT cell line). The effectiveness of the spheroids to be recovered and grown under 2D culture conditions was evaluated. The morphology of the migrated cells from the 3D spheroids was characterized at the nano-microscale through 3D profilometry. The results demonstrated improved adhesion and proliferation in the migrated cells, both advanced properties for regenerative applications.